Republic of Equatorial Guinea : 2010 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2010)
This paper examines key findings of the Republic of Equatorial Guinea's 2010 Article IV Consultation. Real GDP has increased fortyfold since 1995, and large oil revenues have allowed the government to embark on an ambitious infrastructure investment program while amassing foreign savings. Basic infrastructure is being developed, and although achievements in social areas have been muted, expenditure in this area is programmed to rise. The underdeveloped financial system has been unscathed by the global financial turmoil, and appears generally sound.